Erinnerung an Diktatur und Krieg. Brennpunkte des kulturellen Gedächtnisses zwischen Russland und Deutschland seit 1945 - Wirsching, Andreas (Quellen und Darstellungen zur Zeitgeschichte, 2015)
Dictatorship and war unite but also divide historical commemoration in Russia and Germany. Twenty-nine German and Russian authors examine key issues in Russian and German cultures of remembrance and their traumatic dimensions. The book includes classical memorial sites such as Stalingrad, memorials for particular groups, problematic historical sites, and the cinematic engagement with contemporary history.